2019
DOI: 10.1021/acs.analchem.9b02363
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Serodiagnosis of Scrub Typhus Using Surface-Enhanced Raman Scattering-Based Lateral Flow Assay Platforms

Abstract: A surface-enhanced Raman scattering-based lateral flow assay (SERS-LFA) technique has been developed for the rapid and accurate diagnosis of scrub typhus. Lateral flow kits for the detection of O. tsutsugamushi IgG (scrub typhus biomarker) were fabricated, and the calibration curve for various standard clinical sera concentrations were obtained by Raman measurements. The clinical sera titer values were determined by fitting the Raman data to the calibration curve. To assess the clinical feasibility of the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 36 publications
0
44
0
Order By: Relevance
“…It has been demonstrated that the sensitivity of ICT increased by 20% when used in combination with DNA-based loop-mediated isothermal PCR assay (Blacksell et al 2012 ). To achieve the higher sensitivity and accuracy in the diagnosis of scrub typhus, a surface-enhanced Raman scattering-based lateral flow assay (SERS-LFA) has been developed (Lee et al 2019 ). The developed assay can perform the quantitative analysis of samples, which is not possible with the normal lateral flow assay.…”
Section: Diagnosis Of Scrub Typhusmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that the sensitivity of ICT increased by 20% when used in combination with DNA-based loop-mediated isothermal PCR assay (Blacksell et al 2012 ). To achieve the higher sensitivity and accuracy in the diagnosis of scrub typhus, a surface-enhanced Raman scattering-based lateral flow assay (SERS-LFA) has been developed (Lee et al 2019 ). The developed assay can perform the quantitative analysis of samples, which is not possible with the normal lateral flow assay.…”
Section: Diagnosis Of Scrub Typhusmentioning
confidence: 99%
“… ELISA IgM 95.5 88.0 Saraswati et al ( 2019 ) 2. SERS-LFA 56 kDa tissue specific antigen 100 100 Lee et al ( 2019 ) 3. Real-time PCR HtrA 70.5 69.7 Rawat et al ( 2018 ) ELISA IgM IgG 82.7 75 96.4 91 4.…”
Section: Diagnosis Of Scrub Typhusmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we proposed a real-time two-channel surface-enhanced Raman scattering (SERS)-based LFIA biosensor to simultaneously detect anti-SARS-CoV-2 IgM/IgG with high sensitivity. SERS-LFIA strip is a new promising analytical technology that integrates functional SERS-encoded nanoparticles (NPs), also called SERS nanotags, into the LFIA system instead of the commonly used Au NPs as the signal reporter [ [18] , [19] , [20] ]. This technology can offer strong (high-sensitivity), specific (fingerprint feature), and stable (no photobleaching) SERS signals.…”
Section: Introductionmentioning
confidence: 99%
“…However, the inherent defects of conventional LFIA are poor quantitative ability and limited detection sensitivity, which both depend on colorimetric analysis. Increasing attention has been paid to surface-enhanced Raman Scattering (SERS)-based LFIA technology, which combines the high sensitivity and quantitative analysis of SERS technology and the rapidity and convenience of LIFA (Hwang et al, 2016;Lee et al, 2019;Wang et al, 2019b). SERS-based LFIA uses Raman reporter-labeled SERS nanomaterials instead of colloidal Au as the signal tags, thereby providing strong and stable SERS signals (Jia et al, 2018;Khlebtsov et al, 2018).…”
Section: Introductionmentioning
confidence: 99%